"Lean" outreach in the time of COVID-19: using online channels to promote an online service. Issue 3 (3rd July 2021) - Keenan, Caitlin
Abstract: In summer 2020, the library team at Royal Roads University launched a new online tool they were confident would improve the literature search experience for faculty and students. But how could they promote a new point-of-need service without already being present at the point of need? And how do you run an effective outreach campaign in a global pandemic, anyhow? As the author describes, by targeting key audience groups and providing tailored presentations across a range of (digital) channels, the library increased adoption of their new tool by 700 percent over the first 6 months of its availability.